Kafkas Hattı’nda Kurulan Stratejik Rus Kentleri - Müberra Koçyiğit Türk (Coğrafi Bilimler Dergisi)
In the historical context, Tsarist Russia made the Don-Volga, Kuban-Terek rivers the center of military-economic, security and population strategies. In the North Caucasus, local peoples were exiled on the Caucasus line established following the rivers, and fortress cities were established on the northern skirts of the Greater Caucasus Mountains. Tsarist Russia strengthened its position in the region through Russian expansion by benefiting from the supporter population it settled in the region in terms of security, military, trade, socio-cultural and religious aspects. Russian language and culture expanded through these hydropolitical channels. The study examines the reasons and how Tsarist Russia built the Caucasus line and how the fortresses it established here turned into cities. The concrete space method, historical analysis method and geographical determinism theory were used for the study. As a result of the study, it was understood that the ethnic size of the population before the Caucasus War in the cities established in the 18th and 19th centuries on the Caucasus line changed in favor of Russians, Armenians and Ukrainians and that the Russians dominated the region.